Struggling for epistemic and emotional justice—a collaborative autoethnography of personal assistance - Lill Hultman; Maya Hultman (Frontiers in Sociology, 2025)
The present article explores the intersection between disability and the emotions evoked by the experience of living with Personal Assistance (PA) in everyday life. The aim is to explore the emotion work around navigating the emotional and epistemic injustice faced by disabled people and their family members. As family members, mother and daughter, we are bound by our mutual experiences of being recipients of disability support. Research tends to focus on the professional gaze. Hence, the emotion management of disabled people living with disability support and their family members needs to be better understood. Life with PA provides a context that illustrates what epistemic and emotional injustice in various forms feels like. Our narratives may help to increase the understanding of the complex interplay between assistance coordinators, external personal assistants, young adults in need of PA, and family members involved in providing PA in everyday life. Focusing on our experiences of having linked lives underlines the entanglement of having different roles vis-a vis each other. Utilizing a collaborative autoethnographic approach we have identified three themes, The interconnectedness between emotion invalidation and crip time, The expectation of emotion work and Managing conflicting needs in the light of emotion work and linked lives. The findings show a difference concerning the expectation of emotion management, where external PAs perform emotional labor during work hours, while assistance users and family members perform emotion work throughout the day. Professionals often cause epistemic injustice in different situations and increase the need to perform emotion work in implementing PA instead of acknowledging the lived experience of assistance users and family members. When assistance coordinators or external PAs seek to eliminate certain emotions from the experiences of users or their family members, they overlook valuable insights about the situation. Silencing those with lived experiences risks dismissing individuals who possess relevant first-hand knowledge due to their emotional connection to the experienced injustice.